Analisis Daya Saing Usahatani Bawang Merah Antara Musim Hujan dan Musim Kemarau di Kabupaten Bima - Nilasari, Nilasari; Syafiuddin, Syafiuddin; Natsir, Mohammad (Universitas Galuh, 2025)
Horticultural commodities are commodities that have the potential to have increasing economic value and have the potential to continue to be developed. In developing farming with high-value horticultural commodities, one of them is to increase farmer production, namely by developing shallot farming. This study aims to (1) determine private and social benefits and transfer effects using PAM Analysis on shallot farming patterns in Bima Regency; (2) to determine the competitiveness of shallot farming patterns in Bima Regency. The data analysis method used is the Policy Analysis Matrix (PAM) model. The PAM matrix is a policy analysis matrix that functions to measure the efficiency of input use, comparative and competitive advantages and the level of government intervention or interference in an economic activity. The results of this study indicate that shallots in the rainy season have a level of private profit, social profit and transfer effect has a positive value level. This shows that shallots in the rainy season have good efficiency at the price level, so they are worthy of being developed. Meanwhile, shallot farming in the dry season has a positive private profit level, positive social profit and negative transfer effect. This shows that there is no additional producer surplus caused by government policies applied to input and output. Bima Regency in the rainy season and dry season both have comparative advantage and competitive advantage. This shows that shallots in Bima Regency are good to be developed to become superior commodities.